First-row transition metal complexes of a phosphine-silylene- based hybrid ligand - Akhtar, Ruksana; Kaulage, Sandeep H.; Sangole, Mayur P.; Tothadi, Srinu; Parvathy, Parameswaran; Parameswaran, Pattiyil; Singh, Kirandeep; Khan, Shabana (Inorganic Chemistry, 2022)
We have prepared two new silylene-phosphine-based hybrid ligands Si{N(R)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)} [R = TMS {trimethylsilyl} (1) and TBDMS {tert-butyldimethylsilyl} (2)], which possess two donor sites. Furthermore, the treatment of the bidentate ligand 1 with base metal halides {FeBr2, CoBr2, NiCl(2)middotdme [nickel chloride(II) ethylene glycol dimethyl ether]} and 2 with NiBr(2)middotdme [nickel bromide(II) ethylene glycol dimethyl ether] afforded four-coordinate six-membered metal complexes 3-6, respectively, which feature coordination from both Si(II) and P(III) sites. Subsequently, complexes 3 [(FeBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 4 [(CoBr2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], 5 [(NiCl2)Si{N(SiMe3)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}], and 6 [(NiBr2)Si{N((SiBuMe2)-Bu-t)C6H4(PPh2)}{PhC((NBu)-Bu-t)(2)}] are studied for their redox and magnetic properties with the help of UV-vis spectroscopy, cyclic voltammetry, SQUID magnetometry, and theoretical calculations. Complexes 3-6 were found to display a paramagnetic behavior. All the compounds are well established by single-crystal X-ray diffraction studies.